Assessing the reliability and resiliency of the groundwater aquifer system in Chao Phraya River Basin, Thailand - Sharma, Yaggesh Kumar; Shanmugam, Mohana Sundaram; Babel, Mukand Singh; Shrestha, Sangam; Ho Huu Loc; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Based on satellite observations of Earth{u2019}s time variable gravity field from the Gravity Recovery and Climate Experiment (GRACE), it is possible to derive variations in terrestrial water storage, which includes groundwater, soil moisture, and snow. Given auxiliary information on the latter two, one can estimate groundwater storage variations. GRACE may be the only hope for groundwater depletion assessments in data-poor regions of the world. In this study, soil moisture and surface water were simulated by the Global Land Data Assimilation System (GLDAS) & dam storage data and used to isolate groundwater storage anomalies from GRACE water storage data for the Chao-Phraya River basin and its four major sub-basins. The results showed that the GRACE-estimated shallow GWS anomalies during 2002{u2013}2017 agree well with the observed groundwater change anomaly. More than 1300 groundwater wells data has been evaluated in the study. The water in the top most aquifer is not potable due to high salinity occurring since the deposition. In this review, the approaches used for estimating groundwater storage variations are presented along with the main applications of GRACE data for groundwater monitoring. Issues that were related to the use of GRACE-based TWS are also addressed. However, the high production and newly developed wells at the greater depths are mostly served for industrial purposes & other domestic purposes. Due to the past uncontrolled over pumping of groundwater, certain aquifers and overlying clay layer are under substantial stress, leading to serious land subsidence which at its most severe amounts to 0.8 cm/year in Bangkok region. Normalized GRACE-derived groundwater storage deviations are shown to quantify groundwater storage deficits during the GRACE record, which we define as the GRACE Groundwater Drought Index (GGDI). In this research, GGDI is applied over the study area, a regional aquifer undergoing intensive human activities and subject to significant drought periods during the GRACE record. Combining the drought and sustainability indexes, as presented in this work, constitutes a measure for quantifying groundwater sustainability. Hence, Resiliency & reliability has been evaluated by GGDI which is varies 30-35 percent in all 8 sub-basins. This framework integrates changes in groundwater resources due to human influences and climate changes.
Thesis (M. Eng.) - Asian Institute of Technology, 2022
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Keywords: GRACE (Artificial satellites); Groundwater -- Thailand -- Chao Phraya River Basin